2018
DOI: 10.1090/proc/13958
|View full text |Cite
|
Sign up to set email alerts
|

The set of stable primes for polynomial sequences with large Galois group

Abstract: Let K be a number field with ring of integers OK , and let {f k } k∈N ⊆ OK [x] be a sequence of monic polynomials such that for every n ∈ N, the composition f (n) = f1 • f2 • . . . • fn is irreducible. In this paper we show that if the size of the Galois group of f (n) is large enough (in a precise sense) as a function of n, then the set of primes p ⊆ OK such that every f (n) is irreducible modulo p has density zero. Moreover, we prove that the subset of polynomial sequences such that the Galois group of f (n)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…This is still a rather mysterious topic even in the first non-trivial case, which is that of quadratic polynomials. A great amount of interest on the topic has risen in recent years, as witnessed by the numerous papers on the topic, such as [1,3,4,7,9,10,11,12,13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…This is still a rather mysterious topic even in the first non-trivial case, which is that of quadratic polynomials. A great amount of interest on the topic has risen in recent years, as witnessed by the numerous papers on the topic, such as [1,3,4,7,9,10,11,12,13,20,21].…”
Section: Introductionmentioning
confidence: 99%
“…As a specific example, Jones[122, Conjecture 6.3] has conjectured that x 2 + 1 is stable over F p if and only if p = 3, i.e., for f (x) = x 2 + 1, the set (19.3) is {3}. Ferraguti[76] has shown that under some Galois-theoretic assumptions, the set of stable primes (19.3) has density zero.…”
mentioning
confidence: 99%
“…is surjective, and we denote by Ω N its image. More details on the action of Ω N on T N can be found for example in [5,16,22].…”
Section: The Tree Of Roots As a Cayley Graphmentioning
confidence: 99%
“…This gives that Ω ∞ is a pro-2-group. This description is of course just a rephrasing of the usual wreath product formulation used, for example, in [3,5,16,17].…”
Section: The Tree Of Roots As a Cayley Graphmentioning
confidence: 99%